The effect of drought on health outcomes and health expenditures in rural Vietnam - Tobias Lechtenfeld; Steffen Lohmann (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2014)
This paper studies the impact of droughts on health outcomes and health expenditures in rural Vietnam. Given the increasing frequency of extreme weather events in Vietnam and many developing countries, it is crucial for policy makers to be aware of the economic impact of such shocks at the micro level. Using local rainfall data, the analysis directly links the incidence of drought to health shocks and health-related expenditures from a multiple-wave panel of rural Vietnamese households. Overall, the results suggest that individuals affected by drought display a deterioration of health conditions and have significantly higher health expenditures. The effect is found to prevail among households with a high degree of agricultural dependency and limited access to coping mechanisms such as selling assets or tapping off-farm income sources. The preferred estimates using an IV strategy reveal that drought-related health shocks can cause non-negligible additional financial burden for many households vulnerable to poverty in rural Vietnam. This paper quantifies the immediate impact of drought on health conditions and contributes to the existing literature which has mostly focused on the long-term consequences.
Keywords: I15; O15; Q54; 330; climate shocks; drought; health; Vietnam